Consevation of migratory and local birds of satpura hills of Madhya Pradesh (India) - P.K. Mishra (Environment Conservation Journal, 2006)
In the present study a survey of migratory  and  local birds  of satpura  hills  were  examined.  During  the  course  of study  a total of twenty eight species of migratory birds belonging to twenty two families were noticed.